Bed-load transport in vegetated flows : phenomena, parametrization, and prediction - Wu, Haoliang (2022)
This study presents an experimental study on bed-load transport in the presence of emergent vegetation, which is simulated using uniformly sized circular cylinders arranged in a homogeneous distribution. The spatial variability of bed-load fluxes in vegetated flows is first examined. Then a model is proposed for evaluating the bed-load transport rate based on the scour holes that form around the vegetation stems. The influences of spatial variability and intensified turbulence on sediment transport are finally considered by relating the dimensionless transport rate and flow intensity to the stem size and vegetation density. The derived formula for predicting the bed-load transport rate in vegetated flows is applicable for weak to moderate transport conditions.